The Influence of Entrepreneurial Orientation and Market Orientation on Marketing Performance through Competitive Advantage - Satria Pradja, Novi; Iskandar; Masruroh, Rina; Santikawati, Lita; Maulana, Yasir (International Journal Administration, Business & Organization, 2024)
This study aims to determine the influence of entrepreneurial orientation and market orientation on marketing performance through competitive advantage. Respondents in this study were the perpetrators of fries onion IKM, which totals to 35 respondents. The sampling technique is saturated sampling. The path method was employed for the data analysis and the type of research is quantitative method using SPSS 23.0 program. The study result showed that: There is a positive and significant influence of entrepreneurial orientation on competitive advantage, there is a positive and insignificant impact of market orientation on competitive advantage, there is a positive and significant influence of entrepreneurial orientation on marketing performance, there is a positive and insignificant effect of market orientation on marketing performance, there is no impact of competitive advantageon marketing performance, there is no mediating effect among entrepreneurial orientation on marketing performance using competitive advantage, there is no mediating impact among market orientation on marketing performance using competitive advantage.